Analysis on the Seismic Performance of the Fully Bolted Diaphragm-Through Connections to RCFST. Issue 7 (July 2015) - Luo, Song; Wang, Xiaodun; Wang, Xin; Cui, Dongbin; Wu, Liao; Chen, Zhihua
Based on the experimental results of fully bolted diaphragm-through connections composed of concrete-filled steel tubular columns and H-shaped steel beam, 3D nonlinear finite element models were established to analyze the mechanical properties of this new fully bolted diaphragm-through connection using ABAQUS. An analysis was conducted under cyclic loading. A method to estimate the bolt flip platform was presented and used to correct the hysteretic curves for the fully bolted through-diaphragm connections. The failure modes, load-drift, and stiffness degradation curves of the finite element analyses were found to be in good agreement with the tests results.